RECONSTRUCTING THE CURRICULUM AND EDUCATIONAL FRAMEWORK OF MADRASSA BOARDS IN PAKISTAN - Rahman, Khubaib ur; Madani, Asiya; Ramzan, Muhammad Tariq (Humanities & Social Sciences Reviews, 2021)
Purpose of the study: This study highlighted the Islamic Madarsa's role in the modern education system. Methodology: It was library research in which books and Journals are the primary sources of content collection. Interpretation of Philosophies of Islamic Scholars has been made from qualitative analysis. Main findings: The study reveals that Islamic Madarsas play a very positive role in spreading Education according to the needs of hours. Islamic Madarsa education system is handy in achieving the goals. They have a very positive impact on students' learning. Application of the Study: This study will help out the new researchers to think and conduct more studies on the various factors of the Islamic Madarsas education system. Novelty/ originality of the study: Earlier, Madarsa education focused more on traditional learning but in this study focus is more on correlating them with the current situation. There is a need to bring these successful experiments into book form, set rules and regulations so that others can benefit from them, and formulate such a framework based on the results obtained.